Entrepreneurship Character Education in Elementary Schools: Systematic Literature Review (SLR) - Eko Setiono; Zahidah Ismah Nabilah; Febriana Fitri; Aniek Indrawati; Ludi Wishnu Wardana (FKIP, Universitas Palangka Raya, 2023)
Research objectives 1) application of character education 2) Implementation of Entrepreneurship Learning for elementary school formal education students. Character Education, especially at the Elementary School level, in entrepreneurship learning has a big challenge to be able to provide enlightenment to students through the learning process about the need for entrepreneurial behavior that is not only self-interest oriented, but economic behavior that must also be oriented to the interests of the people, through learning. entrepreneurship. The method used in this research is Systematic Literature Review (SLR) by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that Entrepreneurship character education at the Elementary School level applies habituation and cultivation of several entrepreneurial values, namely the value of honesty, Discipline Value, Independent Value, Leadership Value, Creative Value. several models of entrepreneurship learning, namely market day which is routinely carried out by schools. There are 2 main activities carried out by the school in one year, the first is holding a book exhibition bazaar, and a culinary exhibition bazaar by grade 6 students at the end of each semester. Marketday is in the form of a book fair, usually schools cooperate with malls or publishers.